SURF algorithm-based panoramic image mosaic application - Watada, J. (Springer Science and Business Media Deutschland GmbH, 2018)
Panoramic image mosaic is a technology to match a series of images which are overlapped with each other. Panoramic image mosaics can be used for different applications. Image mosaic has important values in various applications such as computer vision, remote sensing image processing, medical image analysis and computer graphics. Image mosaics also can be used in moving object detection with a dynamic camera. After getting the panoramic background of the video for detection, we can compare every frame in the video with the panoramic background, and finally detect the moving object. To build the image mosaic, SURF (Speeded Up Robust Feature) algorithm is used in feature detection and OpenCV is used in the programming. Because of special optimization in image fusion, the result becomes stable and smooth. Â© Springer International Publishing AG 2018.